Statistical Correlation Measures From Higher‐Order Moments in Quantum Oscillator Systems. Issue 5 (24th March 2021) - Salazar, Saúl J. C.; Laguna, Humberto G.; Sagar, Robin P.
Abstract: Triple‐wise and higher‐order correlation measures are proposed using analogies from information theory. Two‐ and three‐variable statistical correlation measures, obtained from higher‐order moments, are examined in three‐particle continuous variable quantum oscillator systems. It is illustrated how the mutual information and cokurtosis measures exhibit similar behaviors, as the strength of the attractive or repulsive interparticle potential is varied. Abstract : Statistical correlation measures in interacting quantum harmonic oscillator systems are explored. Emphasis is placed on measures which detect higher‐order correlations. Cokurtosis measures, based on non‐linear expectation values, exhibit similar behaviors to the mutual information ones from information theory.